1995
DOI: 10.1002/j.1460-2075.1995.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Programming of a repressed but committed chromatin structure during early development.

Abstract: The determination of chromatin for transcription during early development as well as the requirement for trans‐acting factors during this period has been analysed in Xenopus. Basal transcription is repressed both during oogenesis and after the mid‐blastula transition (MBT), and transactivators are required to relieve this repression. In contrast, transactivators cannot overcome the generalized transcriptional repression which occurs in embryos before MBT. However, they do bind to promoters leading to a repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…During this stage, the nuclear envelope is disrupted and p53 can thus access chromatin. Transcriptional repression during early development is mainly due to a dynamic competition between the histones massively present in the egg, and which dominantly repress the assembly of transcription complexes (Prioleau et al, 1994(Prioleau et al, , 1995. This repression phenomenon a ects all types of promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this stage, the nuclear envelope is disrupted and p53 can thus access chromatin. Transcriptional repression during early development is mainly due to a dynamic competition between the histones massively present in the egg, and which dominantly repress the assembly of transcription complexes (Prioleau et al, 1994(Prioleau et al, , 1995. This repression phenomenon a ects all types of promoters.…”
Section: Discussionmentioning
confidence: 99%
“…25 nl of injection mix was injected into germinal vesicles as previously described (Prioleau et al, 1995). Seventeen to 30 oocytes were injected per experimental point.…”
Section: Oocyte Injectionsmentioning
confidence: 99%
“…It is possible that a narrow window exists at exactly the midbastula transition when many genes are initially transcribed even if they then become downregulated until later development. Previous work has suggested that assembly of chromatin versus association of the basal transcription machinery limits transcription prior to the midbastula transition but that specific transcription activators can still access the DNA before this time (Prioleau, 1995). After the midblastula transition, the basal transcription machinery joins to activate transcription but subsequent production of other regulators could then establish developmentally regulated transcriptional programs.…”
Section: Mirna Expression During Zebrafish Developmentmentioning
confidence: 99%
“…TATA-binding protein (TBP) has been identified as a molecule that is able to facilitate transcription before the MBT if two conditions are met (3,37,38): (i) recombinant TBP protein is preincubated with the promoter template prior to injection into embryos, and (ii) a state of incomplete chromatin assembly is present. Such an immature chromatin structure is observed at early time points after injection of a promoter template and after coinjection of a large amount of nonspecific DNA that titrates chromatin assembly.…”
mentioning
confidence: 99%